Methodology series module 4: Clinical trials - Maninder Singh Setia (Wolters Kluwer Medknow Publications, 2016)
In a clinical trial, study participants are (usually) divided into two groups. One group is then given the intervention and the other group is not given the intervention (or may be given some existing standard of care). We compare the outcomes in these groups and assess the role of intervention. Some of the trial designs are (1) parallel study design, (2) cross-over design, (3) factorial design, and (4) withdrawal group design. The trials can also be classified according to the stage of the trial (Phase I, II, III, and IV) or the nature of the trial (efficacy vs. effectiveness trials, superiority vs. equivalence trials). Randomization is one of the procedures by which we allocate different interventions to the groups. It ensures that all the included participants have a specified probability of being allocated to either of the groups in the intervention study. If participants and the investigator know about the allocation of the intervention, then it is called an "open trial." However, many of the trials are not open - they are blinded. Blinding is useful to minimize bias in clinical trials. The researcher should familiarize themselves with the CONSORT statement and the appropriate Clinical Trials Registry of India.